+0  
 
0
226
1
avatar+8 

How I have to proceed here?

5f(-1)-3=

    5f(-1)=3

          5f=3/-1

             f=-3/5

or

5f(-1)-3=

    5f(-4)=

          5f=1/-4

             f=-0,25/5

or

5f(-1)-3=

      5f(3)=

        15f=

           f=1/15

felipebohorquez  Aug 18, 2015

Best Answer 

 #1
avatar+92437 
+5

5f(-1)-3=

 

You question is a bit confusing.    

If f is just a normal variable then

5f(-1)-3

=5*f*-1    -3

=-5f-3

 

However, if  f(-1) means function of -1 then you cannot simplify it without more information.   

Melody  Aug 19, 2015
Sort: 

1+0 Answers

 #1
avatar+92437 
+5
Best Answer

5f(-1)-3=

 

You question is a bit confusing.    

If f is just a normal variable then

5f(-1)-3

=5*f*-1    -3

=-5f-3

 

However, if  f(-1) means function of -1 then you cannot simplify it without more information.   

Melody  Aug 19, 2015

20 Online Users

avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy